IDENTIFIKASI DAN UJI FITOKIMIA EKSTRAK ALAMI TANAMAN ANTIUROLITHIASIS - Tami Oktari; Fitmawati '; Nery Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
In Indonesia, medicinal plants have been used to treat several diseases including kidney stone disease (urolithiasis). Urolithiasis is caused by the accumulation of substances inhuman urine that will form a stone, which consists of solid microlite. This stone can grow bigger if it is not treated. The kidney stone problem is the third problem after urine tract and prostate infection. Therefore, it is necessary to find out the treatment for this disease, including by using the potential plants for antiurolithiasis such as Hibiscus rosa-sinensis, Hibiscus tilliaceus, Sonchus arvensis, Sida rhombifolia, Strobilanthus crispus, and Tristaniopsis whiteana. The purpose of this study was to compare the effectiveness of six medicinal plants in dissolving kidney stones using in vitro methodand to identify their secondary metabolites that have the best potential as antiurolithiasis agent. Two tests were caried out, i.e. phytochemical test and in vitro test for detecting plant extract activity in disolving kidney stone. The extract used was pure extract. The kidney disolving test was performed at 37°C for 3 hours with 15 minutes agitation. The result of phytochemical test showed that Sonchus arvensis and Sida rhombifolia had the highest secondary metabolite content. The in vitro assay showed that all of six tested plants could disolve kidney stone. Two species (Hibiscus tilliaceus and Sonchusarvensis) gave the lowest weight of kidney stone, however there was no significant difference in each treatment (P>0,05).